SA-7 Os Humerus Amputation in Cat with Osteomyelitis - E Fitriana; D Ardiansyah; D U Rahmiati; . Gunanti (Hemera Zoa, 2018)
Osteomyelitis is bone inflammation caused by infectious agent such as bacteria, fungi, or viruses [1]. Infectious agent attacks part of the bone such as cortical bone, periosteum, and myeloid cavity. Osteomyelitis cases may happen through two causes: hematogenous infection or infection right to the bone after trauma [2]. Staphylococcus sp., Streptococcus sp., and Escerichia coli are bacteria most often cause bone infection [3]. Around 50% of osteomyelitis cases are caused by the bacteria Staphylococcus [1]. Treatment for osteomyelitis cases depends on the severity of the case. If it is still mild, veterinarians may only give antibiotic to curb infection. However, on more severe osteomyelitis cases (usually on chronic osteomyelitis), other than antibiotic treatment, debridement or amputation surgery may be performed [4].                Amputation is a surgical procedure performed to separate a part or entire body part or extremities [5]. This procedure is a last option when problems on one part of the body cannot be treated by any other procedure. Several example cases that put amputation as a treatment option are bad blood circulation which cause no blood to sustain the tissues and thus causing tissue death; severe injury (from accidents); tumor/cancer; congenital or acquired defects that cannot be treated; and serious infection that cannot be treated by any other treatment [6].